2021
DOI: 10.1017/s0266467421000122
|View full text |Cite
|
Sign up to set email alerts
|

Nowhere to escape – Diversity and community composition of ferns and lycophytes on the highest mountain in Honduras

Abstract: IPCC predictions for Honduras indicate that temperature will increase by up to 3–6°C and precipitation will decrease by up to 7–13% by the year 2050. To better understand how fern and lycophyte communities might be affected by climate change, we comprehensively surveyed the community compositions of ferns and lycophytes at Celaque National Park, the highest mountain in Honduras. We surveyed a total of 80 20 × 20 m2 plots along an altitudinal gradient of 1249–2844 m a.s.l., identifying all species and estimatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 90 publications
2
7
0
Order By: Relevance
“…Rather, it appears that the low ability of ferns to regulate water loss (Brodribb and McAdams, 2011) and to optimize CO2 assimilation (Flexas et al, 2014) result in the higher drought-sensitivity in ferns compared to angiosperms. One might thus assume that in a world of climate change, fern diversity will follow temperature increases and move toward higher elevations and latitudes (Bystriakova et al, 2014;de Gaspar et al, 2021;Reyes-Chávez et al, 2021;Pie et al, 2022). While this is certainly true in general terms, the well-known relationship of fern diversity to climate is a correlative one, and the underlying causal mechanisms are still poorly known.…”
mentioning
confidence: 99%
“…Rather, it appears that the low ability of ferns to regulate water loss (Brodribb and McAdams, 2011) and to optimize CO2 assimilation (Flexas et al, 2014) result in the higher drought-sensitivity in ferns compared to angiosperms. One might thus assume that in a world of climate change, fern diversity will follow temperature increases and move toward higher elevations and latitudes (Bystriakova et al, 2014;de Gaspar et al, 2021;Reyes-Chávez et al, 2021;Pie et al, 2022). While this is certainly true in general terms, the well-known relationship of fern diversity to climate is a correlative one, and the underlying causal mechanisms are still poorly known.…”
mentioning
confidence: 99%
“…More generally, discrepancies between ERA5 and historical simulations may partly be due to structural differences between the single realization of real-world climate variability and the ensemble mean forced response [44]. Overall, both ERA5 and CESM2-Historical display climate speeds beyond Preindustrial variability and within the range of midcentury SSP2-4.5, consistent with known historical and expected future ecosystem stress from warming [1,3,6,7,28,29].…”
Section: Relative Ecological Risk From Climate Speedsmentioning
confidence: 69%
“…Observed range shifts track temperature trends from internal climate variability regardless of their sign, strongly indicating both cooling and warming are ecologically relevant [1,34]. While relicts that temporarily survive warming through persistence or by sheltering in microclimates [27,28] would likely benefit from rapid cooling, numerous ecosystems that have transitioned to a new state under warming may be suddenly jeopardized. Paleoclimatic data indicates periods with rapid (interannual to multidecadal) large-scale cooling following a long-term warming trend coincide with planetary-scale changes to ecosystems [49,50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same was observed in a study with ferns and lycophytes in Honduras, found that 28-53% of these will have altitudinal displacement by the year 2100 for both RCP 2.6 and RCP 8.5, respectively 34 . Another study found that 47% of the fern and lycophyte species found along the mountain of the Celaque National Park, the highest in Honduras, will have to shift their distribution above the maximum altitude of the mountain under the scenario from RCP2.6 to the year 2050 35 . This displacement to areas of higher altitudes is also being recorded for animal species.…”
Section: Discussionmentioning
confidence: 99%